Modelling the Influence of Corotating Interaction Regions on Jovian MeV-electrons. (July 2015) - Vogt, A; Effenberger, F; Fichtner, H; Heber, B; Kleimann, J; Kopp, A; Potgieter, M S; Sternal, O; Wiengarten, T
Abstract: Corotating Interaction Regions (CIRs) are recurrent structures in the solar wind characterized by velocity jumps and a magnetic field compression. Since the 1970s it is known that Jupiter is a quasicontinuous source of MeV-electrons dominating the flux in the inner heliosphere. In connection with CIRs, this flux is modulated mainly by changing propagation conditions in the inner heliosphere. In order to model these recurrent variations in Jovian electron intensity the VLUGR3-Code was used to solve Parker's Transport Equation. The diffusion as well as the solar wind speed are modelled from 0.1 to 50 AU. Two different approaches are used, one derived by Kissmann (2002) and another by Giacalone et al (2002) which was further developed. The simulation results are compared to IMP-8 electron count rates to investigate the differences of the two solar wind models in the propagation code.